Microstructural and electric properties of bismuth-layered structured ceramics - SrBi2(Ta1-xNbx)O-9 - Zanetti, S. M.; Bueno, Paulo Roberto [UNESP]; Sotilo, VCM; Leite, E. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Trans Tech Publications Ltd, 2002)
Ceramic samples of SrBi2(Nb1-xTax)O-9 (0 less than or equal to x less than or equal to 1) were prepared by the solid state reaction method in order to investigate their structural and electrical features as well as obtain useful information to improve the properties of SrBi2(Nb1-xTax)O-9 as a thin film. The X-ray diffraction patterns and the scanning electronic microscopy photomicrographs show no secondary phases but the formation of a solid-state solution for all the composition. The ac conductivity of the samples, measured at 25 degreesC and 100 kHz frequency, decreases with the increase of Ta content. Such results were explained by intrinsic conductivity of pure components.
Keywords: bismuth layer; SrBi2(Nb1-xTax)O-9; ceramics; ferroelectric